Development of a blockchain-based electronic voting system utilizing national identification number - Bismark, Olabode Idowu-; Oshin, Oluwadamilola; Adetiba, Emmanuel (Institute of Advanced Engineering and Science, 2025)
Traditional voting methods in Nigeria face numerous challenges, including logistic issues, security concerns, and allegations of fraud, which undermine public trust. This work develops a blockchain-based electronic voting system (EVS) that leverages the national identification number (NIN) for biometric verification to address these issues. The research identifies the limitations of current blockchain voting solutions, such as implementation complexity, scalability issues, user adoption resistance, and cybersecurity threats and provide a more secure and user-friendly alternative. The system integrates blockchain technology with biometric verification to create an immutable, transparent, and secure voting process. The methodology involves designing a system architecture that includes a blockchain network, an NIN verification module, and a user interface (UI). Users register using their NIN, authenticate themselves, and cast their votes, which are then encrypted and recorded on the blockchain. The system's functionality was tested using tools like Ganache for local blockchain development, MetaMask for Ethereum wallet integration, and Solidity for writing smart contracts. Results from the implementation indicate significant improvements in security, transparency, and user accessibility compared to traditional voting systems. The user authentication test achieved a 100% valid login success rate and 0% invalid login attempts. Meanwhile, the voting test accuracy was 100%.